Using the security triad to assess blockchain technology in public sector applications. (June 2020) - Warkentin, Merrill; Orgeron, Craig
Highlights: Blockchain technology has security, governance, and regulatory implications for government. The Confidentiality-Integrity-Accessibility (CIA) provides useful insight for managers. A major advantage of blockchain technology is non-reputability. Abstract: This conceptual paper explores the impact of blockchain technology on public sector processes through the lens of information security. It includes an overview of the evolution of e-government, a synopsis of existing applications of blockchain technology, and innovative blockchain developments. We utilize the Confidentiality-Integrity-Accessibility (CIA) triad to guide our discussion of the security, governance, and regulatory implications of this technology. Leveraging the CIA triad model, we provide context for public managers who may consider blockchain technologies, and we highlight certain advantages arising from the "non-reputability" of distributed ledgers. In particular, we highlight the advantages of blockchain technologies with regards to non-reputability to help public managers understand how to best leverage blockchain technology to transform operations.